Development of a Biotechnology Module to Improve Science Communication Skills Toward Society 5.0 - Kurniasih, Septi; Taufik, Annisa Novianti; Nulhakim, Lukman; Juansah, Dase Erwin (Jurnal Penelitian dan Pembelajaran IPA, 2022)
The need for teachers who are proficient in communicating science face-to-face and making flexible use of various integrative media is increasing along with changes in community communication patterns. High scientific communication skills can support learning with topics closely related to the latest technology, such as biotechnology. This study aims to develop a multimedia-based biotechnology module using Canva as a learning source to increase prospective science teachers in Science Education Department in science communication skills toward Society 5.0 era. As a result, the learning resource developed as a Biotechnology module for S1 Science Education students contains integrated biotechnology content. It presents learning activity guides, quizzes, and assignments that support prospective teachers in developing science communication skills in the classroom. Validation results from material and media experts indicate that this module is valid and feasible to be applied in biotechnology learning for prospective science teachers.